THE EFFECT OF PERFORMANCE APPRAISAL, COMPENSATION, AND JOB SATISFACTION TO EMPLOYEE ENGAGEMENT AT STIKES DR. SOEBANDI JEMBER - Ariefa Quinta Hanum; Yuniorita Indah Handayani; Supardi Supardi (STIE Mandala Jember, 2022)
The purpose of this study was to analyze the effect of Performance Appraisal, Compensation,and Job Satisfaction either partially or simultaneously on Employee Engagement on STIKES dr.Soebandi. This type of research is quantitative research, with the type of data used is primarydata. The sampling technique used the census technique, with a total sample of 86 respondents.The data analysis method used multiple linear regression analysis. The results of the analysisshow that partial job appraisal has no significant effect on employee engagement because itproduces a significance level above 0.05. Then, the partial compensation has a significant effecton employee engagement because it produces a significance level below 0.05. Then, the partialjob satisfaction has a significant effect on employee engagement because it produces asignificance level below 0.05.